State of digitalization among traders of informal seed in Tanzania - Steinke, Jonathan; Van Etten, Jacob; Kalemera, Sylvia; Mutua, Mercy; Rubyogo, Jean-Claude; Ochieng, Justus (2024)
Key messages: • Traders of grain and informal seed in Tanzania have limited experience with internet-enabled services, but 96 % own a mobile phone. Besides phone calls, digital services play no significant role in business activities, however. • Traders rely primarily on verbal communication with other traders for important information, including market prices, grain demand, and consumer trait preferences. • Traders have modest interest in employing digital solutions for marketing products to new customers. This may constitute an entry point for digital solutions that lead to accelerated uptake of new crop varieties. • Traders could compile consumer feedback about new varieties through simple digital channels. Aggregated insights about consumer preferences and demand may help de-risk other traders’ decisions on buying and selling a new variety.